1999
DOI: 10.1038/sj.ijo.0800893
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms responsible for the attenuation of diabetic and obese conditions in ob/ob mice treated with dopaminergic agonists

Abstract: OBJECTIVE: We previously reported that a two week treatment with SKF 38393 (SKF, a dopamine D 1 receptor agonist), plus bromocriptine (BC, a dopamine D 2 receptor agonist) acted synergistically to normalize hyperphagia, body fat, hyperglycaemia and hyperlipidaemia in obaob mice. The present study further investigates the biochemical mechanisms triggered by this drug treatment. DESIGN: Six week old female C57BLa6J obaob mice were divided into three groups and treated for two weeks with either BC and SKF, vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 30 publications
8
51
0
1
Order By: Relevance
“…The stimulated area under the oral glucose tolerance test curve was reduced by 46% while the stimulated area under the insulin curve was reduced by 30%. Treatment with SKF 38393 (dopamine D1 receptor agonist) plus BC (dopamine D2 receptor agonist) acted synergistically to normalize hyperphagia, body fat, hyperglycemia and hyperlipidemia in leptin-deficient Ob/Ob mice (12). This treatment not only normalized hyperphagia but redirected several metabolic and endocrine activities independent of its effects on feeding to improve the obese/diabetic syndrome in Ob/Ob mice.…”
Section: Discussionmentioning
confidence: 92%
“…The stimulated area under the oral glucose tolerance test curve was reduced by 46% while the stimulated area under the insulin curve was reduced by 30%. Treatment with SKF 38393 (dopamine D1 receptor agonist) plus BC (dopamine D2 receptor agonist) acted synergistically to normalize hyperphagia, body fat, hyperglycemia and hyperlipidemia in leptin-deficient Ob/Ob mice (12). This treatment not only normalized hyperphagia but redirected several metabolic and endocrine activities independent of its effects on feeding to improve the obese/diabetic syndrome in Ob/Ob mice.…”
Section: Discussionmentioning
confidence: 92%
“…However, D2 receptors involvement in sucrose intake was not elucidated. On the one hand, previous studies reported that systemic [60] [61] [62] and intracerebral [63] bromocriptine administration in insulin-resistant animals, declined hepatic glucose production and gluconeogenesis, reduced adipose tissue lipolysis, and improved insulin sensitivity [43]. On the other hand, Hajnal et al [15] reported that D2 receptors were involved in heightened sucrose intake observed in the OLETF obese rat.…”
Section: Discussionmentioning
confidence: 97%
“…These include reduced DA concentrations, impaired response to electrically evoked accumbal DA release, decreased basal tyrosine hydroxylase and DAT expression, as well as lower levels of D 2 receptor binding (Pothos et al, 1998;Geiger et al, 2008). Correspondingly, striatal D 2 receptor binding is inversely correlated to the degree of obesity in humans (Volkow and Wise, 2005), and D 2 receptor agonists produce hypophagia and weight loss in animal models of obesity (Scislowski et al, 1999;Davis et al, 2008). In addition, mesolimbic D 3 receptor function may also have a role in obesity, as suggested by findings of D 3 receptor agonist-induced hypophagia in DIO mice and increased adiposity in D 3 receptor knockout mice (McQuade et al, 2003;McQuade et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that positive modulation of D 1 receptor function contributed to the anorexic effect of tesofensine is in agreement with the role of D 1 receptor receptors on feeding behavior. Accordingly, D 1 receptor stimulation reduces food intake and weight gain in mouse models of obesity (Scislowski et al, 1999;Bina and Cincotta, 2000;Kuo, 2002). The inhibitory effect of D 1 receptor activation on feeding is most likely linked to stimulated hypothalamic DA function, which can lead to suppression of hypothalamic orexigenic signaling (Kuo, 2002;Alberto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation